BALANCED SCORECARD: EVALUATION OF ACCURACY TIME TO STRATEGY IMPLEMENTATION - Sri Maryati; supriyadi supriyadi (Optimum: Jurnal Ekonomi dan Pembangunan, 2018)
The purpose of this study was to examine performance evaluation BSC-based and general bias reduction in financial performance evaluations when there is actual and planned time conformity and absence of actual and planned time conformity. Using experiments with 2 x 1 design between subjects. Participants in this study amounted 50 students. Using of ANOVA and Paired-Sample T-Test analysis, The analysis show that general bias BSC financial performance evaluation can be derived when managers receive information on time to strategy implementation. On the other hand, the existence of time strategy implementation information is not able to give more weighted differences to nonfinancial performance. The results are consistent and confirm the findings of Johnson, Reckers & Bartlett (2014